Single stage acrylic acid obtaining based on methanol and acetic acid - Nebesnyi, Roman; Shpyrka, Iryna; Shatan, Anastasiia-Bohdana; Lukiyanchuk, Andriy; Ivasiv, Volodymyr; Nebesna, Yuliia; Lapychak, Nazariy (Lviv Polytechnic Publishing House, 2015)
The new complex oxide acid type catalysts were developed and their performance in the process of aldol condensation of acetic acid with formaldehyde to acrylic acid was studied. The optimum conditions of the process were determined. It was established that these catalysts are effective in the process of methanol to formaldehyde oxidation, and also in the process of single stage acrylic acid obtaining from acetic acid and methanol in the presence of air.
Keywords: aldol condensation; oxidation; catalysts; acrylic acid; acetic acid; methanol; formaldehyde